Sterile-α- and Armadillo Motif-Containing Protein Inhibits the TRIF-Dependent Downregulation of Signal Regulatory Protein α To Interfere with Intracellular Bacterial Elimination in Burkholderia pseudomallei-Infected Mouse Macrophages - Baral, Pankaj (American Society for Microbiology, 2013)
Burkholderia pseudomallei, the causative agent of melioidosis, evades macrophage killing by suppressing the TRIF-dependent pathway, leading to inhibition of inducible nitric oxide synthase (iNOS) expression. We previously demonstrated that virulent wild-type B. pseudomallei inhibits the TRIF-dependent pathway by upregulating sterile-α- and armadillo motif-containing protein (SARM) and by inhibiting downregulation of signal regulatory protein α (SIRPα); both molecules are negative regulators of Toll-like receptor signaling. In contrast, the less virulent lipopolysaccharide (LPS) mutant of B. pseudomallei is unable to exhibit these features and is susceptible to macrophage killing. However, the functional relationship of these two negative regulators in the evasion of macrophage defense has not been elucidated. We demonstrated here that SIRPα downregulation was observed after inhibition of SARM expression by small interfering RNA in wild-type-infected macrophages, indicating that SIRPα downregulation is regulated by SARM. Furthermore, this downregulation requires activation of the TRIF signaling pathway, as we observed abrogation of SIRPα downregulation as well as restricted bacterial growth in LPS mutant-infected TRIF-depleted macrophages. Although inhibition of SARM expression is correlated to SIRPα downregulation and iNOS upregulation in gamma interferon-activated wild-type-infected macrophages, these phenomena appear to bypass the TRIF-dependent pathway. Similar to live bacteria, the wild-type LPS is able to upregulate SARM and to prevent SIRPα downregulation, implying that the LPS of B. pseudomallei may play a crucial role in regulating the expression of these two negative regulators. Altogether, our findings show a previously unrecognized role of B. pseudomallei-induced SARM in inhibiting SIRPα downregulation-mediated iNOS upregulation, facilitating the ability of the bacterium to multiply in macrophages.